Effects of repeated oral doses of ketoconazole on a sequential ascending single oral dose of fedratinib in healthy subjects - Ogasawara, Ken; Xu, Christine; Kanamaluru, Vanaja; Palmisano, Maria; Krishna, Gopal (Cancer chemotherapy and pharmacology, 2020)
Purpose Fedratinib is an orally administered Janus kinase 2-selective inhibitor that is indicated for the treatment of adult patients with intermediate-2 or high-risk myelofibrosis in the United States. Fedratinib is metabolized by multiple cytochrome P450s (CYPs) in vitro, with the predominant contribution from CYP3A4. The primary objective of this study was to evaluate the effects of 14-day repeated 200 mg twice daily (BID) oral doses of a strong CYP3A4 inhibitor, ketoconazole, on a sequential ascending single oral dose of fedratinib in healthy male subjects. Methods An open-label, fixed-sequence, two-treatment cross-over study was conducted. Two cohorts of healthy adult males received two single doses of fedratinib (50 mg in Cohort 1 and 300 mg in Cohort 2) with one dose administered alone on Day 1 of Period 1 and the other dose coadministered with ketoconazole in the morning of Day 6 of Period 2. Subjects in both cohorts received 200-mg BID (Days 1–14) ketoconazole during Period 2. Results Coadministration of repeated 200-mg BID oral doses of ketoconazole for 14 days increased fedratinib exposure by 3.85- and 3.06-fold for area under the plasma concentration–time curve from time zero to infinity following a single oral dose of fedratinib of 50 and 300 mg, respectively. Oral administration of a single dose of 50 or 300 mg of fedratinib, administered alone or coadministered with steady-state ketoconazole, was safe and tolerable in the healthy male subjects. Conclusions These results serve as the basis for fedratinib dose reduction when fedratinib is coadministered with strong CYP3A4 inhibitors.